IMF Lending in an Interconnected World - Poulain, Jean-Guillaume.; Reynaud, Julien (Washington, D.C. : International Monetary Fund, 2017)
We analyze the determinants of IMF lending since the early nineties, a period during which the roles of financial cycles and interconnectedness as amplifiers and transmitters of economic crises have gained prominence. First, we show that the global financial cycle is an important driver of IMF lending cycles. Second, using a panel of 91 advanced, emerging, and frontier economies over 1992-2014, we show that global factors and interconnectedness, as proxied by a countries' potential exposure to economic spillovers from trade partners, together with more traditional idiosyncratic factors, have a significant impact on the probability that a member country obtains financial assistance from the IMF. Our results are robust to various robustness checks. The approach presented in this paper can be used to assess future demand for IMF financial assistance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet